Insects in water towers: Hibernating flies could compromise microbial drinking water quality - Baele, Amber; Waegenaar, Fien; De Maeyer, Katrien; De Gusseme, Bart; Vervaeren, Han; Spanoghe, Pieter; Boon, Nico (Frontiers in Water, 2023)
Providing safe and qualitative drinking water is becoming increasingly important due to climate change and population growth. Water towers are often used to provide storage and ensure water pressure. However, microbial regrowth of water is still a challenge during storage and distribution. Moreover, water towers can be used as an aggregation site by insects, mainly flies (Diptera). In this study, ten water towers in Belgium were monitored for eight months with sticky traps to evaluate fly species diversity, abundances and activity. The results showed the presence of three fly species: Thaumatomyia notata (yellow swarming fly), Musca autumnalis (face fly) and Pollenia spp. (cluster fly). The flies entered the towers in autumn and took shelter against wintering conditions in cracks and crevices, especially on the highest floors where the water tank is located. In this way, flies can come into contact with the drinking water. Based on the monitoring campaign, a risk assessment matrix was set up to determine risks of possible microbial water contaminations caused by flies in water towers. This was validated by a worst-case experiment in laboratory conditions. Face flies (living and dead) were added to tap water to evaluate their influence on microbial water quality and safety using several techniques such as 16S rRNA amplicon sequencing, flow cytometric cell counts and fingerprinting. Our research showed that flies in drinking water promote bacterial growth and change the phenotypic resident drinking water community. Furthermore, new genera such as Pseudomonas and Acinetobacter as well as the coliforms Serratia fonticola and S. liquefaciens were detected when flies were added to tap water. Hence, prevention and intervention measures are important in water quality management to avoid contact between flies and drinking water in water towers. In this study, several effective prevention methods are discussed, such as sealing ventilation, overflow and weep holes with insect screens with adequate mesh size and covering water tanks.